What a difference a mentally-toughening off-season makes: a case of NCAA DI rowers - Stamatis, A.; Papadakis, Z. (International Journal of Sports Science, 2018)
Non-contact injuries in US collegiate athletics during offseason have increased. Despite the widespread acceptance of mental toughness (MT) training in the strength and conditioning world, coaches do not tend to measure the effectiveness of their regimens. Strength and conditioning coaches (SCC) tend to design mostly physical and not psychological protocols to increase MT. Purpose: Triggered by current incidents in Big 12, in Pac-12, and most recently, in Big Ten -in which SCCs were purportedly involved, researchers attempted to investigate the effectiveness of an offseason physical training protocol on the MT levels of Division I rowers. Methods: Fourteen student-athletes and their strength and conditioning coach (multi-rating) assessed, via Qualtrics, the players` levels of MT using the Mental Toughness Index (MTI). Results: No statistically-significant effect was found between pre- and post-offseason intervention [F (1, 54) = 0.13, p = 0.71] nor between the perception of that effect between players and coach [F (1, 54) = 1.23, p = 0.27]. Conclusions: The levels of athletes` MT between the pre- and post-intervention measurements did not increase significantly and the perceptions of the assessors were not significantly different either. Therefore, the results suggest that the intervention did not work in regard to increasing the MT levels of the team. Furthermore, the MTI scores indicate coach-athlete compatibility in recognizing this theoretical construct. In an effort to support the student-athletes` well-being and avoid similar media backlash, more similar research projects are crucial so as to move from anecdotally-based to evidence-based strength and conditioning MT training protocols. However, during that attempt, coaches need to share their protocols for reasons of evaluation and replication.